Digital design techniques and its effectiveness in contemporary fashion fabric " Pixel art model" (Al-Academy, 2026)
Digital design techniques are one of the types of modern digital design techniques for the development of design innovations based on various techniques, including pixel art technology-the research includes the following question:- Do pixel art digital design techniques achieve effectiveness in Contemporary fashion fabric design? The research aims at: defining pixel art techniques for digital design and their effectiveness in women's fashion fabric designs, addressing digital design techniques in women's fashion fabric designs- The second chapter contained two researchers: digital design techniques in fashion fabric designs, the effectiveness of digital design techniques in fashion fabric designs, and the third chapter: research procedures by adopting the descriptive approach in analyzing the sample, the research tool was to prepare the analysis axes form and then analyze the models, and the fourth chapter: the research results are the most important:-the element of the square geometric shape-digital design has achieved vitality and movement with a variety away from monotony in digital fabric designs in general and digital fashion fabric designs in particular